(untitled) (ModaPalavra e-periódico, 2025)
The fast fashion clothing industry organizes its mass production based on outsourcing, which promotes a rapid production flow. In this context, the practice of outsourcing is important in the contemporary scenario, leading outsourced companies to innovate in processes, machinery and technologies, as well as, subcontracting, in turn, labor to intensify their forces with the contractor. In this environment, fourth-party companies emerge, hired for administrative management, that is, selecting, hiring and controlling outsourced services. The objective of this article is to address labor relations in the process of outsourcing, subcontracting and fourth-party contracting for the production of fast fashion clothing. It is a qualitative and descriptive research, with technical procedures for data collection based on bibliographic research, and subsequent qualitative analysis of the data. It was found that the production model based on outsourcing expanded due to the productive need of fast fashion clothing companies, with outsourcing emerging as a business strategy of collaboration, by transferring its productive activities to third parties – which, in turn, subcontract their services. The results indicate that the subcontracted companies do not have an employment relationship or partnership with the company that hires the outsourced services. For the outsourcing process, fourth-party management was implemented, a new management structure, which manages the labor relations between the contracting company and the outsourced company, not related to the companies subcontracted by the outsourced companies.